The southern Afar: A household economics study - Tilahun, N. (International Livestock Centre for Africa, 1983)
Presents results of a study to describe & quantify the Afar production system in terms of its ability to support the human population, w. an analysis of the demographic characteristics of households, economic activities pursued by members and determination of their viability, i.e. balance between levels of food production (milk offtake) & food consumption (grain purchases) and ability to meet energy requirements of members in a study area within the northeast rangelands of Ethiopia.